2021
DOI: 10.1111/desc.13150
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on executive functions and intelligence in middle childhood

Abstract: Executive functions (EFs) and intelligence (IQ) are phenotypically correlated. In twin studies, latent variables for EFs and IQ display moderate to high heritability estimates; however, they show variable genetic correlations in twin studies spanning childhood to middle age. We analyzed data from over 11,000 children (9-to 10-year-olds, including 749 twin pairs) in the Adolescent Brain Cognitive Development (ABCD) Study to examine the phenotypic and genetic relations between EFs and IQ in childhood. We identif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 73 publications
3
18
0
Order By: Relevance
“…Univariate twin models revealed that additive genetic and nonshared environmental influences explained differences in measures of EF in middle childhood. Heritability estimates on the Flanker Task, Continuous Performance Task, and Digit Span Backward were generally lower than, but comparable with, previous studies of children and adolescents (e.g., Freis, Morrison, Lessem, et al, 2022; Polderman et al, 2006; Schachar et al, 2011). It is possible that in-home versus lab administration and variations of the task could have contributed to differences in heritability estimates.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Univariate twin models revealed that additive genetic and nonshared environmental influences explained differences in measures of EF in middle childhood. Heritability estimates on the Flanker Task, Continuous Performance Task, and Digit Span Backward were generally lower than, but comparable with, previous studies of children and adolescents (e.g., Freis, Morrison, Lessem, et al, 2022; Polderman et al, 2006; Schachar et al, 2011). It is possible that in-home versus lab administration and variations of the task could have contributed to differences in heritability estimates.…”
Section: Discussionsupporting
confidence: 79%
“…The first goal was to examine the genetic and environmental influences on established measures of EF (Flanker Task, Continuous Performance Task, and Digit Span Backward) and EC (parent-reported Attentional Focusing and Inhibitory Control) in our sample of demographically diverse twin children to compare with previous research. We hypothesized that additive genetic and nonshared environmental influences would explain differences in EF and parent-reported Inhibitory Control (Friedman et al, 2008; Freis, Morrison, Lessem, et al, 2022; Polderman et al, 2006) and that parent-reported Attentional Focusing would be highly heritable with evidence of nonadditive genetic influences (Lemery-Chalfant et al, 2008). The second goal was to assess the genetic and environmental overlap between individual measures of EF and EC, as well as between latent variables of EF and EC.…”
Section: Commonalities and Distinctions Between Ef And Ecmentioning
confidence: 99%
“…First, associations between intelligence and Common EF were explained by both genetic influences (total broad-sense genetic correlation; r g = .44) and nonshared environmental influences ( r e = .60). The broad-sense genetic correlation ( r g = .44, 95% CI [.28, .59]) was similar in magnitude to the additive genetic correlations observed in older adolescents (age 17; r a = .57; CIs not reported; Friedman et al, 2008) and middle-aged adults (age 56; r a = .59, 95% CI [.56, 1.00]; Gustavson, Panizzon, Franz, et al, 2018) but was smaller than those observed in younger adolescents (age 10: r a = .86; 95% CI [.45, 1.27]; Freis et al, 2021; age 11: r a = .92; 95% CI [.72, 1.11]; Engelhardt et al, 2016). Even with the extended family design employed here, there was still low power to detect whether the strong genetic correlation was driven by additive genetic influences and dominance genetic influences.…”
Section: Discussionsupporting
confidence: 68%
“…The above conclusions would account for the fact that phenotypic and genetic associations between Common EF and intelligence approach unity in childhood and early adolescence (Brydges et al, 2012;Engelhardt et al, 2016;Freis et al, 2021) but weaken somewhat in later adolescence and adulthood (Friedman et al, 2008;. The factor structure of EFs appears to be unitary in children before about age 10-12 (Brydges et al, 2014;Hartung et al, 2020;Xu et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation